MDVLab: in volo sull'Antartide (GEOmedia, 2010)
MDVLab: a flight over AntarcticaThe Flight Mechanics Laboratory (MDVLab) of the University of Bologna was born in 2006 at the Second Faculty of Engineering. The research activity mainly covers problems of modeling, simulation and control of atmospheric and spatial flight. Thanks to the intense collaboration with the National Institute of Geophysics and Volcanology (INGV), the workgroup has extended its knowledge beyond the aerospatial field, showing a wide offer of technologies for the Observation of the Earth. An important project in wich MDVLab is involved with INGV regards the use of unmanned aircrafts for magnetic field measurements in Antarctica; in this paper the acquisition system is described and the first experimental results are shown.